Burden of morbidity in patients with Ebstein anomaly: a two-country, population-based cohort study including 823 patients. (3rd October 2022) - Eckerstrom, F; Dellborg, M; Hjortdal, V E; Eriksson, P; Mandalenakis, Z
Abstract: Background: Burden of morbidity in patients with Ebstein anomaly (EA) is to a large extent undescribed. Purpose: We conducted an extensive two-country register-based collaboration aiming to describe the burden of morbidity in patients with EA. Methods: Patients born in the period 1930–2017 and diagnosed with EA were identified in Danish and Swedish nationwide medical registries and subsequently merged. Each EA patient was matched by birth year and gender with ten controls without congenital heart disease from the general population. Cox proportional hazard regression model was used to compute risk (hazard ratio (HR)) of morbidity (arrhythmia, heart failure, and stroke). Follow-up started at birth. Patients and controls became at risk at birth. Results: We included 823 patients and 8, 230 matched controls; median follow-up was 13.2 years (interquartile range: 3.5–20.9). In the total EA cohort, 44% (n=366) underwent cardiac surgery, predominantly EA-related surgery (81%) and other congenital cardiac surgery (15%). Approximately half of the cohort had an isolated EA (n=442) and 13% (n=108) had a concomitant atrial septal defect (ASD) only. Patients with non-operated isolated EA had a 9-fold increased risk of arrhythmia and a 5-fold increased risk of heart failure compared with the general population [HR for arrhythmia 9.4 (95% CI: 6.9–12.7) and HR forheart failure 5.2 (95% CI: 3.2–8.3)]. The risk of arrhythmia, heart failure, and stroke among patients with non-operated EA and concomitant ASD was 12.1 (95% CI: 3.0–48.8), 30.6 (95% CI: 3.2–295.2), and 8.2 (95% CI: 0.7–91.2), respectively. The risk of stroke in operated EA patients with concomitant ASD was 43.8 (95% CI: 17.5–109.7). Patients with operated isolated EA had a 25-fold increased risk of developing arrhythmia and 10-fold increased risk of heart failure compared with the general population [HR for arrhythmia 25.0 (95% CI: 17.7–35.3) and HR for heart failure 10.1 (95% CI: 6.0–16.9]. Conclusion: Patients with EA carries a substantial burden of arrhythmia, heart failure, and stroke compared with the general population irrespective of treatment pathway, necessitating meticulous follow-up in specialized adult congenital heart disease clinics to detect and possibly prevent or limit morbidity at an early stage. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Novo Nordic Foundation.